Using Entropy to Measure Religious Pluralism - George Sturm (Entropy)
This paper discusses a unique and revolutionary method that quantitatively evaluates the programming of a media outlet regarding religious pluralism. Using a “program appeal” score and entropy measures from information theory, the broadcast operator is able to determine if governmental compliance is being met and whether certain programs are problematic. The theoretical foundation of this tool is presented and illustrated using real-life data.